Granger causality between money, output, prices and interest rates: Some cross-country evidence from the period 1875 - 1984 - Pentti Pikkarainen; Matti Virén (Bank of Finland, 1989)
This paper studies the Granger causality between money, output, prices and nominal interest rates by making use of long time series from 11 countries. Empirical analyses, both in the time and frequency domain, suggest that money does not help in predicting movements in output over time. In fact, only in the cases of Canada, Italy and Norway there seems to exist a unidirectional causation from money to real output. A quite different result emerges with money and prices. Thus, typically causation runs from money to prices during the sample period.
URN:NBN:fi:bof-201807301761
Keywords: 330